Performance, noise and emission characteristics of DI engine using canola and Moringa oleifera biodiesel blends using soluble multiwalled carbon nanotubes. (1st April 2021) - Manigandan, S.; Gunasekar, P.; Praveenkumar, T.R.; Sabir, Jamal S.M.; Mathimani, Thangavel; Pugazhendhi, Arivalagan; Brindhadevi, Kathirvel
Graphical abstract: Abstract: An experimental study was carried out for determining the performance, noise and emission characteristics of two cylinder diesel engine powered by Canola and Moringa oleifera blends. Tests were conducted at different engine speeds for different fractions of 20%, 40% and 100% vol of blends. Further, the effects of adding 40 mg/l Multiwalled carbon nanotubes (MWCNT) by ultrasonication were examined. The properties of M. oleifera complied with ASTM D6751. Over the different engine speeds, 2100 rpm reported the optimized values of brake power, NOx and smoke opacity. Provided that, the BTE and BSFC of all blends doesn't record a profound change compared to diesel. However, addition of the MWCNT improvised the combustion and performance characteristics of the diesel engine irrespective of engine speeds. On compelling all performance and emission parameters, M. oleifera reported superior results than canola blends. Regarding the combustion noise, there was no significant difference between the two blends observed. However, the addition of blends increased the combustion noise and it was up to 2% by the addition of nanoadditives. The procured results clearly show that the use of M. oleifera and canola not only enhances the performance but also acts an antioxidant additive for the biodiesel blends.